Perancangan Aplikasi Mobile Pembelajaran Bahasa Berbasis Podcast dan Penerapan Hybrid Recommender System - Anugerah, Rico Putra; Nugroho, Budi; Al Haromainy, Muhammad Muharrom (UNIVERSITAS RAHARJA, 2025)
This research develops a mobile application based on podcasts to enhance language skills, particularly in listening. Listening is considered a priority because vocabulary comprehension is necessary before mastering speaking, reading, and writing. Podcasts are chosen as the learning medium due to their ability to present audio on specific topics, aiding users in more effectively understanding the language. The application is also equipped with a recommendation system that utilizes the Hybrid Recommender System method, tailoring content based on user behavior and content similarity. The research results show that this application can optimize language learning, with a particular focus on language learning through podcasts, and helps users improve their language skills with a precision value of 85,6%, recall 85,9%, F1-Measure 88% and 80,2 for SUS testing.